ENGINE BALANCING AND COUNTERWEIGHTING OF CRANKSHAFTS - Umidov, Lazizkhon (International Conference on Science, Education & Law, 2025)
This paper explores the principles and practices of engine balancing and counterweighting of crankshafts, focusing on their critical role in enhancing engine performance and longevity. Through a detailed review of fundamental theories and practical approaches, the study examines the impact of imbalances and counterweights on vibration, wear, and fuel efficiency. Key concepts such as oscillating and rotating masses, periodic forces, and engine torque balancing are thoroughly analyzed. Insights into computational methods and modern engineering techniques are discussed to provide a comprehensive understanding of the subject, supported by illustrative diagrams.